Elevated serum concentration of monocyte chemotactic protein 4 (MCP‐4) as a novel non‐invasive prognostic and predictive biomarker for detection of metastasis in colorectal cancer. Issue 4 (28th June 2016) - Okugawa, Yoshinaga; Toiyama, Yuji; Mohri, Yasuhiko; Tanaka, Koji; Kawamura, Mikio; Hiro, Junichiro; Araki, Toshimitsu; Inoue, Yasuhiro; Miki, Chikao; Kusunoki, Masato
Abstract : Purpose: Despite recent progress in the diagnosis and treatment of colorectal cancer (CRC), the prognosis remains poor, and metastatic recurrence is the leading cause of poor prognosis. We systemically evaluated the levels of differentially‐expressed serum cytokines using array‐based techniques to identify a novel and reliable serum biomarker with which to predict metastasis and poor outcomes of CRC. Methods: We examined cytokine profiling using preoperative serum from two different cohorts to identify differentially‐expressed serum cytokines in patients with metastatic CRC. In the validation phase, serum monocyte chemotactic protein‐4 (MCP‐4) concentration was assessed in 194 patients by enzyme‐linked immunosorbent assay, and its relationships with clinicopathological findings were investigated. Results: In discovery phase, three cytokines were differentially expressed in serum from patients with metastatic CRC. In validation phase, high MCP‐4 was significantly associated with older age, advanced T stage, distant metastasis, and UICC stage. Cox regression analysis showed that elevated MCP‐4 was an independent prognostic factor of disease‐free survival and overall survival. Furthermore, logistic regression analysis revealed that high serum MCP‐4 was an independent predictor of distant metastasis. Conclusion: Quantification of serum MCP‐4 concentration might support the early detection/prediction of recurrence and may contribute to the prediction of clinical outcomes in CRC. J. Surg. Oncol. 2016;114:483–489 . © 2016 Wiley Periodicals, Inc.